Hubungan antara Self Image Dengan Fear of Missing Out pada Mahasiswa Pengguna Facebook - Dipayani (Arus Jurnal Pendidikan, 2023)
Abstract: his research was conducted to see whether there is a relationship between Self Image and Fear Of Missing Out on Facebook user students at Tama Jagakarsa University. The Self Image variable is measured by the Self Image Scale created by Jersild (2012) and the Fear Of Missing Out variable is measured by the Fear Of Missing Out Scale created by Przybylski, Murayama, Denhaan and Gladwell (2013). This study involved 150 student subjects using Facebook at Tama Jagakarsa University using incidental sampling techniques. This study uses the Pearson Product Moment analysis method with the help of the SPSS application version 20.0 for Windows. The results showed that there was a significant relationship in a negative direction between Self Image and Fear Of Missing Out on Facebook user students at Tama Jagakarsa University.